Manipulating the formation of cesium lead bromide nanocrystals via oleic acid. Issue 8 (9th February 2023) - Wang, Miao; Yu, Qiyu; Yu, Tian; Zhang, Sijie; Gong, Min; Liu, Yuehui
Abstract : The phase-selective controlled synthesis of Cs4 PbBr6 and CsPbBr3 nanocrystals was realized by adjusting the dosage of oleic acid. Abstract : To realize the precise modulation among the cesium lead halide perovskite-related phases is one of the most fascinating subjects and has motivated increasing research. The formation mechanisms of different phases of cesium lead halide have not been fully recognized. In this work, we reported the phase-selective synthesis of CsPbBr3 nanorods and Cs4 PbBr6 nanocrystals (NCs) in amine-free systems, simply by adjusting the dosage of oleic acid (OA). By utilizing UV-visible absorption spectroscopy, we probed the evolution of the NCs and some lead bromide complex species during syntheses in reaction systems with different OA dosages. An OA-limited condition facilitated the formation of [PbBr4 ] 2− and Cs4 PbBr6 NCs. OA-rich conditions facilitated the formation of [PbBr3 ] −, [Pb2 Br5 ] −, etc. at early stages and the subsequent generation of CsPbBr3 NCs. As the reaction systems equilibrated at a later stage, as-prepared CsPbBr3 or Cs4 PbBr6 NCs would coexist with certain lead bromide complexes. OA dosage also greatly affected the kinetics of reactions toward CsPbBr3 NCs. A relatively large amount of OA would accelerate the formation of CsPbBr3 NCs. Our experimental results support two-step formation pathways of the cesium lead bromide NCs going through lead bromide complexes, and suggest that OA exerted all the influence by virtue of the lead bromide complexes. Our study presents a relatively clear picture of the formation of CsPbBr3 and Cs4 PbBr6 NCs, which should be helpful in improving the preparation of lead halide perovskite-related NCs.